PERAMALAN DAN PERINGATAN DINI BANJIR KOTA SOLO BERDASARKAN DATA HUJAN - , BONDAN WAHYUSARI KUSUMO; , Prof. Dr. Ir. Sri Harto Br., Dip.H. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Flood disaster in Solo or Surakarta on December 26, 2007 was one of big events beside that in year 1966. The flood peak in December 2007 reached 2075 m3/s while flow capacity at Jurug was 1500 m3 /s. The objectives of this study are to analyze rainfall depth which will most likely cause flood in Surakarta, the expected warning time available to mitigation actions, and to analyze the possibility of flood forecasting and warning system. This study was using HEC-HMS to model the Upper Bengawan Solo watershed, spread from spillway of Wonogiri Dam to Jurug at Surakarta. Catchment area of Wonogiri Dam was not modeled, only the outflow to the downstream area instead, which was assumed to be constant 0 and 400 m3 /s. Flood forecasting was held for rainfall with annual exceedance probability 0.5